Analisis Preferensi Konsumen dan Proksimat Cookies Bebas Gluten Berbahan Baku Tepung Ubi Kayu (Manihot utilissima) Tinggi Protein - Zukryandry Zukryandry; Beni Hidayat; Dayang Berliana (Journal of Food System & Agribusiness, 2019)
The development of cookies products using high-protein cassava flour has never been conducted by a small industry. Industry players do not have information on consumer responses to cookies made from high-protein cassava flour with the addition of palm sugar. This study aimed to analyze consumer preferences and proximate analysis of cookie products with various levels of palm sugar additions. This research used cross section data where the sampling was carried out by accidental sampling as many as 25 panelists. The method used was a multi-attribute analysis of fishbein, and proximate analysis was conducted on best products. The results showed that the panelists preferred F1 cookies products (added by 25% palm sugar) with positive values, and overall this means that consumers' attitudes towards F1 cookies products were considered good. The addition of palm sugar as much as 25% produces cookies with a moisture content, protein content, fat content, fiber content, ash content and carbohydrate content of 3.39%, 4.11%, 27.6%, 9.67, 1.32% and 64.56% respectively.Keywords: Cookies, Preferences, Fishbein, Proximate